PENYITAAN DALAM PERKARA PIDANA DI POLRESTA DENPASAR - Agus Pande Wirajaya, I Gede; Keneng, I Ketut; Manik Pinatih, S.L.P. Dawisni (Kertha Semaya : Journal Ilmu Hukum, 2013)
The aims of seizure who conducted by the investigator are to take over and keep unmovable or movable goods, tangible or intangible assets for the sake of verification in the investigation, prosecution and judicature. The Investigators in perform confiscation should be accompanied by permit of confiscation from the head of the local District Court. The head of the district court have right to refuse requests confiscation from the investigator as a function of control or authority of the head of the district court, in order to avoid unnecessary seizure. In conduct seizure the investigators often find obstacles finally able to reveal a crime.
Keywords: seizure, investigator, the head of the local District Court